Circumscribing the prostitute : the rhetorics of intertexuality, metaphor, and gender in Jeremiah 3.1-4.4 /: the rhetorics of intertexuality, metaphor, and gender in Jeremiah 3.1-4.4. (©2004) - Unknown
No abstract available